Teaching Tourism Communication Skills through Guessing Game at Porodisa Learning Center Manado - Agustinus Lumettu; Treesje L Runtuwene; Robert D Towoliu (HOSPITALITI DAN PARIWISATA, 2019)
Although English is taught in all levels of education in Indonesia starting from Primary Education, English command of the majority of students is poor after learning for at least 6 years during the Junior and Senior High School levels or for the total of 10 years for other students who study English starting from the third grade of Elementary School or even for 11 years for those who go to university and have English subject for two semesters. This poor result is, of course, caused by many factors such as the teacher, the student, the curriculum, the facility, the methodology, etc. Considering that methodology might be one of the causes of failure, the researchers applied guessing game in teaching communication skills at Porodisa Learning Center Manado. The objectives of this research are to find out whether Guessing Game (1) is effective to motivate the students to communicate in English, (2) can improve the students’ grammatical command, and (3) can increase the students’ vocabulary. The method used in this research was qualitative method and the data analysis used was descriptive qualitative method. The data were collected through guided interview, observation and documentation while the sample was taken using purposive sampling technique. The results of the research show that: Guessing game is very effective for teaching communication skills. This game can also improve the learner’s grammatical command and it is also useful for increasing the learners’ vocabulary.